Oral Focal Mucinosis: A Case Report and Literature Review - Farzaneh Agha-Hosseini; Maryam-Sadat Sad (Islamic Dental Association of Iran, 2018)
Introduction: Oral focal mucinosis (OFM) is the soft tissue counterpart of cutaneous fo-cal mucinosis (CFM) and is often misdiagnosed as an oral myxoma. OFM occurs during the fourth and fifth decades of life, predominantly in women (two females per male). Case Report: A 22-year-old lactating female presented with a growing painless, sessile tumor with pale pink color and a lobulated surface with ulcers at the depths of interlobular fissures in the premolar-molar area of the left mandibular alveolar ridge, dating back one year. The tumor was completely excised. No recurrence was observed during the follow-ups over the next three years. Conclusion: The current case appears to be the only one with an OFM reported during the breastfeeding period; therefore, the role of hormonal factors in the pathogenesis of the lesion should be taken into consideration.